1998
DOI: 10.1099/0022-1317-79-4-705
|View full text |Cite
|
Sign up to set email alerts
|

Low level or absent in vivo replication of hepatitis C virus and hepatitis G virus/GB virus C in peripheral blood mononuclear cells.

Abstract: To investigate which subsets of peripheral blood mononuclear cells (PBMCs) are susceptible to infection with hepatitis C virus (HCV) and hepatitis G virus (HGV) or GB virus C (GBV-C), a PCR-based assay using tagged primers in the core region (HCV) and NS3 region (HGV/GBV-C) for the specific detection of negative strand (replicating) viral RNA sequences was developed. In liver biopsy samples both positive and negative strands of HCV RNA were detected, at levels ranging from 3 to 11i10 6 RNA copies per 10 6 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 42 publications
7
92
0
Order By: Relevance
“…Although several early studies found HPgV RNA in liver biopsies, virus was subsequently detected in spleen, bone marrow, cerebrospinal fluid and PBMCs, as noted above (Chivero et al, 2014;George et al, 2006; Kisiel et al, 2013;Mellor et al, 1998;Pessoa et al, 1998;Radkowski et al, 2000;Tucker et al, 2000). Studies attempting to find evidence of HPgV replication in liver tissue were either negative or inconclusive (Berg et al, 1999;Fan et al, 1999;Laskus et al, 1997).…”
Section: Hpgv Tropismmentioning
confidence: 97%
“…Although several early studies found HPgV RNA in liver biopsies, virus was subsequently detected in spleen, bone marrow, cerebrospinal fluid and PBMCs, as noted above (Chivero et al, 2014;George et al, 2006; Kisiel et al, 2013;Mellor et al, 1998;Pessoa et al, 1998;Radkowski et al, 2000;Tucker et al, 2000). Studies attempting to find evidence of HPgV replication in liver tissue were either negative or inconclusive (Berg et al, 1999;Fan et al, 1999;Laskus et al, 1997).…”
Section: Hpgv Tropismmentioning
confidence: 97%
“…HCV transcripts have been observed at low levels in DCs and other lymphoid cells (35,36) but these do not seem to represent significant reservoirs of HCV. However, L-SIGN and DC-SIGN interactions may contribute to immune dysregulation, including the impaired DC function observed in chronic HCV infection (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is supported by the demonstration of HCV replication in hematopoietic cells inoculated into severe combined immunodeficiency mice. 16 Moreover, whereas HCV RNA-negative strand rarely is detected in peripheral-blood mononuclear cells from healthy subjects, 17,18 it commonly is found in HIV-coinfected patients or liver transplant recipients. 9,19 We speculate that HCV infection of the CNS may provide the biological substrate for neuropsychiatric syndromes associated with this viral infection.…”
Section: Discussionmentioning
confidence: 99%